Performance tests and microstructure‐based sigmoid model for a three‐coil magnetorheological damper - Yang, Yang; Xu, Zhao‐Dong; Guo, Ying‐Qing; Sun, Chun‐Li; Zhang, Jie (Structural control and health monitoring, 2021)
Summary Magnetorheological (MR) damper is one of the most promising smart devices for dissipating seismic energy and reducing structural vibrations. The MR dampers with multiple coils are widely adopted to enhance the output damping forces and seismic performance. In order to study the dynamic characteristics of multicoil MR dampers from a micro to macro viewpoint, a three‐coil MR damper was designed and manufactured in this paper. The performance tests of the three‐coil MR damper under different excitation currents, displacement amplitudes, frequencies, and coil combinations were conducted. Assuming that the distance between two adjacent ferromagnetic particles meets chi‐square distribution, the two‐column micromodel for the MR fluid was modified by introducing a distribution parameter. The modified MR fluid micromodel was verified by comparing the damping forces calculated by this model with experimental data. Combining the modified micromodel for the MR fluid and the double‐sigmoid model for MR dampers, a mathematical model for the three‐coil MR damper was proposed. The microstructure‐based sigmoid model considers the effects of yield shear stress of the MR fluid and internal magnetic induction intensity on the damping force. The comparison of the proposed model and the performance test data shows that the microstructure‐based sigmoid model can finely describe the dynamic characteristics and magnetic saturation properties of the three‐coil MR damper under different excitation currents and loading conditions, which provides a good basis for control strategies and dynamic analysis of structures with multicoil MR dampers.